Norway and Its Obligations under ILO 169 – Some Considerations after the Recent Stjernøy Supreme Court Case - Ravna, Øyvind (Arctic Review on Law and Politics, 2016)
Published version. Source at http://dx.doi.org/10.17585/arctic.v7.583 The Norwegian Supreme Court recently pronounced its first ruling on a case which started with investigations by the Finnmark Commission. The Stjernøy Case1 arises from a title claim to land used as pasture by two groups of Sámi reindeer herders. A contributory reason for the claim was that there are mining activities on the island, from which the landowner is entitled to benefit according to the Norwegian Mineral Act. The Supreme Court ruling raises some fundamental questions, among others: what is the significance of ILO 169 in relation to the Finnmark Act?